Two-dimensional antibacterial biocatalyst with photothermal conversion capability and preparation method and application thereof

By doping Fe single atoms and O atoms on 2D MoS2 nanosheets, combined with photothermal conversion technology, the problem of low delivery efficiency of existing antibacterial materials on bacterial biofilms is solved, and efficient ROS delivery and antibacterial effects are achieved, demonstrating that The therapeutic ability comparable to vancomycin.

CN119215936APending Publication Date: 2024-12-31SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411338515.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

When existing antibacterial materials face bacterial biofilms, it is difficult to achieve efficient ROS delivery and antibacterial effects, mainly due to the short ROS life and the weak interaction between the materials and bacteria, they cannot effectively penetrate the biofilm.

Method used

A 2D MoS2 nanosheet (FeO-MoS2) doped with Fe single atoms and introduced O atoms was designed to enhance the catalytic performance and delivery efficiency of ROS through photothermal conversion technology, and use near-infrared light irradiation to generate thermal effects to form tiny holes. Improve the delivery efficiency of ROS.

Benefits of technology

The efficient delivery of ROS to bacterial cells is achieved, which significantly enhances the antibacterial effect and shows wound handling capabilities comparable to vancomycin in animal experiments, providing a potential strategy for non-antibiotic antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215936A_ABST
    Figure CN119215936A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of antibacterial biocatalysts, and particularly relates to a two-dimensional antibacterial biocatalyst with photothermal conversion capacity as well as a preparation method and application of the two-dimensional antibacterial biocatalyst. The two-dimensional antibacterial biocatalyst is a 2D MoS2 nanosheet doped with a Fe single atom and introduced with an O atom to coordinate with Fe. An O-coordinated Fe monatomic site (FeO-MoS2) is designed on the 2D MoS2 nanosheet, so that the ROS catalytic performance of the material is improved, ROS can be more effectively delivered to the surfaces of bacteria in a biological membrane by utilizing a photo-thermal perforation effect, and bacteria in the biological membrane are killed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of antibacterial biocatalysts, and specifically relates to a two-dimensional antibacterial biocatalyst with photothermal conversion capability, a preparation method and an application thereof. Background Art

[0002] The number of patients with bacterial infections in my country is very large. In clinical treatment, long-term use of antibiotics can easily lead to bacterial resistance, thereby increasing the difficulty of treatment. The continuous increase in bacterial resistance has weakened the therapeutic effect of many traditional antibiotics, making bacterial infections difficult to control, resulting in high mortality and economic losses, and posing a serious threat to human health and world public health. In response to the above problems, people need to develop new non-antibiotic strategies to cope with the challenges of antibacterial treatment. In recent years, studies have found that enzyme-mimicking nanomaterials that can mimic the catalytic production of reactive oxygen species (ROS) by natural enzymes can kill bacteria and destroy biofilms, and have great application prospects in the field of anti-resistant bacteria treatment. However, on the one hand, pathogenic bacteria are easy to colonize on the surface of objects, forming biofilms that are difficult to remove. The extracellular polymers (EPS) secreted by bacteria in the biofilms may cut off the nanomaterials on the biofilms and reduce the antibacterial efficiency; on the other hand, ROS have a short lifespan and are easily quenched, and have a short migration distance in the solution. The existing enzyme-mimicking material interface has weak interactions with bacteria, and cannot achieve in situ efficient ROS antibacterial. This study focuses on solving this problem by enhancing the delivery of ROS in biofilms.

[0003] In biomedical applications, in addition to physical structures, there are many other methods to achieve substance delivery. Among them, photo / thermal pore technology is an effective method. This method uses the local thermal effect generated by the laser to cause local phase change of the lipid bilayer or overall protein denaturation, forming tiny holes in the cell membrane, allowing foreign substances to enter the cell. In anti-biofilm research, the same photothermal delivery method can be used to overcome the two barriers of EPS and internal bacterial membrane structure, enhance the permeability of biofilm and bacterial membrane structure, so that ROS can more effectively reach the bacterial cells and kill bacteria inside the biofilm. To use photothermal delivery of ROS to fight pathogenic biofilms attached to the surface, the following factors need to be considered: (1) The material needs to provide as large a contact area with the biofilm as possible to give full play to the material's photothermal enhancement of the permeability of the biofilm and bacterial membrane structure. (2) The material's catalytic sites should be fully designed to further improve its catalytic ROS production effect. The high surface / volume ratio of ultrathin two-dimensional (2D) materials provides an opportunity to construct and expose more ROS active sites, and their high surface utilization efficiency can enhance their interaction on small-scale surfaces and increase the contact area with biomembranes. Therefore, ROS-based photothermal 2D sheet nanosystems are very suitable for ROS-catalyzed delivery of antibacterial agents to enhance biomembrane permeability.

[0004] Therefore, there is an unmet need in the art to develop new ROS-based photothermal 2D sheet nanosystems. Summary of the invention

[0005] In order to solve the above problems, in one aspect, the present invention provides a two-dimensional antibacterial biocatalyst (abbreviated as FeO-MoS2 in this article) with photothermal conversion capability, wherein the two-dimensional antibacterial biocatalyst is a 2D MoS2 nanosheet doped with Fe single atoms and introduced with O atoms to coordinate with the metal.

[0006] Furthermore, the 2D MoS2 nanosheets doped with Fe single atoms and introduced with O atoms to coordinate with Fe have a 1T phase structure and contain Fe-O, Fe-S and Fe-Mo coordination structures.

[0007] Furthermore, the two-dimensional antibacterial biocatalyst is prepared as follows:

[0008] (1)FeMo6O 24 Preparation of precursor: (NH4)6Mo7O 24 4H2O reacts with Fe salt in water under heating and pH 2.5-3 to obtain FeMo6O 24 Precursor;

[0009] (2) Preparation of two-dimensional antibacterial biocatalyst FeO-MoS2: FeMo6O 24 The precursor reacts with thioacetamide in water under heating conditions to obtain a two-dimensional antibacterial biocatalyst FeO-MoS2.

[0010] Furthermore, the Fe salt in step (1) includes Fe(NO3)3·9H2O.

[0011] Furthermore, the reaction in step (1) is carried out at 80-100°C.

[0012] Furthermore, the reaction in step (1) is carried out for 1-5 hours.

[0013] Furthermore, step (1) further comprises collecting the crude product by filtration after the reaction is completed, recrystallizing it in hot water, and then drying it.

[0014] Furthermore, the reaction in step (2) is carried out at 160-200°C.

[0015] Furthermore, the reaction in step (2) is carried out for 12-36 hours.

[0016] Furthermore, step (2) also includes collecting the reaction product after the reaction is completed, and washing and drying the reaction product.

[0017] In another aspect, the present invention provides the use of the two-dimensional antibacterial biocatalyst having photothermal conversion capability as described herein in the preparation of an enzyme-mimicking preparation.

[0018] Furthermore, the enzyme-mimicking preparation is a peroxidase-mimicking preparation and / or a haloperoxidase-mimicking preparation.

[0019] In another aspect, the present invention provides the use of the two-dimensional antibacterial biocatalyst having photothermal conversion capability as described herein in the preparation of an antibacterial system.

[0020] Furthermore, the antibacterial system may be an antibacterial system against biofilm.

[0021] Furthermore, the antibacterial system also includes H2O2.

[0022] Furthermore, the antibacterial system also includes a near-infrared lighting system.

[0023] Preferably, the antibacterial system also includes H2O2 and near-infrared lighting system.

[0024] In another aspect, the present invention also provides the use of the two-dimensional antibacterial biocatalyst with photothermal conversion capability as described herein in combination with H2O2 in the preparation of an antibacterial system.

[0025] Furthermore, the antibacterial system may be an antibacterial system against biofilm.

[0026] In another aspect, the present invention also provides the use of a two-dimensional antibacterial biocatalyst with photothermal conversion capability as described herein in combination with a near-infrared illumination system in the preparation of an antibacterial system.

[0027] Furthermore, the antibacterial system may be an antibacterial system against biofilm.

[0028] In another aspect, the present invention also provides the use of a two-dimensional antibacterial biocatalyst with photothermal conversion capability as described herein in combination with H2O2 and a near-infrared illumination system in the preparation of an antibacterial system.

[0029] Furthermore, the antibacterial system may be an antibacterial system against biofilm.

[0030] In another aspect, the present invention provides an antibacterial system, which includes the two-dimensional antibacterial biocatalyst with photothermal conversion capability described herein.

[0031] Preferably, the antibacterial system further comprises H2O2.

[0032] Preferably, the antibacterial system also includes a near-infrared lighting system.

[0033] Preferably, the antibacterial system also includes H2O2 and near-infrared lighting system.

[0034] Preferably, the antimicrobial system is an antimicrobial system against biofilm.

[0035] As used herein, the near-infrared illumination system includes a near-infrared laser.

[0036] Furthermore, the power density of the near-infrared laser is 1-5 W·cm -2 , the irradiation distance is 1-10cm, and the irradiation time is 1-10min.

[0037] Furthermore, the H2O2 may be an aqueous H2O2 solution with a concentration of 0.1-0.5 mM.

[0038] Beneficial effects of the present invention

[0039] The present invention uses a polyoxometalate template method to design an O-coordinated Fe single atom site (FeO-MoS2) on a 2D MoS2 nanosheet, thereby improving the ROS catalytic performance of the material and utilizing the photothermal perforation effect to more effectively deliver ROS to the bacterial surface inside the biofilm, thereby killing bacteria in the biofilm. When catalyzing H2O2, its V max Value (1.57×10 -7 M.s -1 ) and TON value (4.03×10 -3 s -1 ), which is superior to most reported metal oxides, single-atom catalysts and metal nanoparticles. XPS and XAS results show that the introduction of O atoms shortens the distance between Fe atoms and Mo atoms, adjusts the band structure of FeO-MoS2, and may optimize the catalytic reaction process. At the same time, under the irradiation of 808nm near-infrared light, FeO-MoS2 has a photothermal conversion effect. Bacterial experiments show that the FeO-MoS2 structure can make the polymer matrix outside the bacterial membrane loose, and the photothermal response ability will cause local phase changes in the bacterial lipid structure, forming tiny holes in the cell membrane, so that the ROS generated by the material catalysis can be efficiently delivered into the bacterial cells. Animal experiments show that the material has a wound treatment ability comparable to vancomycin. This two-dimensional nanosheet structure with ROS catalytic activity with photothermal effect will become a potential candidate for non-antibiotic anti-biofilm strategies. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic diagram of the synthesis of FeO-MoS2 is shown.

[0041] Figure 2 Scanning electron microscope (SEM) images of FeO-MoS2 and comparative materials are shown.

[0042] Figure 3 Shown are (a) high magnification HAADF-STEM image and (b) EDX Mapping image of FeO-MoS2.

[0043] Figure 4 Shown are (a) atomic resolution HAADF-STEM image of FeO-MoS2. (b) corresponding atomic distances in (a). (c) intensity image of the 3D atomic arrangement of a randomly selected area.

[0044] Figure 5 The Raman spectrum curve of each sample is shown.

[0045] Figure 6 Shown are (a) the fitted spectra of Fe 2p and (b) the oxidation state statistics of Fe for each group of samples; (c) the fitted spectra of Mo 3d and (d) S2p.

[0046] Figure 7 (a) Fe K-edge XANES spectrum is shown. The inset is the enlarged XANES spectrum. Fe K-edge EXAFS fitting curves corresponding to (b) FeO-MoS2 and (c) Fe / MoS2 in R space.

[0047] Figure 8 Shown are (a) UV-visible absorption spectra and (b) absorbance values ​​at 652 nm of different samples after reaction with TMB+H2O2.

[0048] Fig. 9 (a) Michaelis-Menten curves of FeO-MoS2 and Fe / MoS2; (b, c) linear double reciprocal plots and V max And TON value statistics.

[0049] Fig.10 The EPR curves of different samples are shown.

[0050] Fig.11 (a) Fluorescence spectra and (b) fluorescence intensity at 610 nm after different catalytic systems and HE reactions. (a) Fluorescence spectra and (b) fluorescence intensity at 435 nm after different catalytic systems and TA reactions.

[0051] Fig.12 Figure 2 shows (a) UV-visible absorption spectra of different samples after reaction with CB and (b) relative catalytic performance of HPO. 520 nm / I 650 nm ratio.

[0052] Fig.13(a) Infrared thermal imaging and (b) temperature changes of FeO-MoS2, Fe / MoS2, MoS2, and Control are shown. (c) UV-visible absorption spectra after NIR irradiation to detect ROS generation.

[0053] Fig.14 Confocal fluorescence images of RD10 / DAPI staining of FeO-MoS2 and biofilms after different treatments are shown.

[0054] Fig.15 The red fluorescence intensity of MRSA biofilm after different treatments is shown.

[0055] Fig.16 Shows C11-BODIPY of FeO-MoS2 and bacteria after different treatments 581 / 591 Confocal fluorescence images of the probe.

[0056] Fig.17 Green fluorescence intensity indicating the level of MRSA lipid peroxidation in the biofilm after treatment with different materials is shown.

[0057] Fig.18 MRSA biofilms treated with different concentrations of FeO-MoS2 are shown, and the biomass was measured by measuring the absorbance of crystal violet staining at 590 nm.

[0058] Fig.19 Shown are the (a) infrared thermal imaging and (b) temperature changes of FeO-MoS2, Fe / MoS2, and MoS2 co-cultured with MRSA biofilms after NIR irradiation.

[0059] Fig. 20 (a) 3D confocal imaging of biofilms treated with FeO-MoS2+H2O2, FeO-MoS2+NIR, and FeO-MoS2+H2O2+NIR (green: live bacteria, red: dead bacteria, blue: EPS). (b) Relative EPS content of MRSA biofilms after different treatments. (c) Green and red fluorescence intensity of MRSA in biofilms after different treatments. (d) Bactericidal ratio of different treatments.

[0060] Fig.21 Live / dead cell staining images of HUVECs treated with MoS2+H2O2, Fe / MoS2+H2O2, and FeO-MoS2+H2O2 after incubation for 1h, 24h, and 48h are shown.

[0061] Fig. 22Live / dead cell staining images of HUVECs treated with MoS2+H2O2+NIR, Fe / MoS2+H2O2+NIR, and FeO-MoS2+H2O2+NIR after incubation for 1h, 24h, and 48h are shown.

[0062] Fig.23 Photographs of wound healing at 12 days in the groups treated with saline (Control), H2O2, FeO-MoS2+H2O2, FeO-MoS2+NIR, FeO-MoS2+H2O2+NIR, and vancomycin are shown.

[0063] Fig.24 (a) Near-infrared photographs and (b) wound temperature changes of the saline (Control), FeO-MoS2+NIR, and FeO-MoS2+H2O2+NIR treatment groups are shown.

[0064] Fig.25 (a) Photos of MRSA agar plates of wounds after different treatments and (b) Statistical analysis of MRSA colony counts on agar plates.

[0065] Fig.26 Shown are (a) leukocyte and (b) neutrophil counts of peripheral blood of experimental rabbits.

[0066] Fig. 27 Shown are (a) H&E staining images of epidermal tissue sections of experimental rabbits in each group after 12 days of recovery; (b) Masson trichrome staining images; (c) CD31 immunohistochemistry staining images and (d) DAPI / CD31 staining three-dimensional reconstruction images and corresponding maximum intensity projection (MaxIP) images (scale bar 50 μm).

[0067] Fig.28 The following table shows the (a) collagen volume value of wound tissue in each group after 12 days of recovery; (b) CD31 expression rate in wound tissue and (c) the number of CD31 positive blood vessels.

[0068] Fig.29 H&E staining of visceral tissue sections (heart, liver, spleen, lung, and kidney) of experimental rabbits after 12 days of treatment is shown.

[0069] Fig.30 A scanning electron microscope (SEM) image of the material prepared in Comparative Example 3 is shown.

[0070] Fig.31 The POD-like catalytic activity of the materials prepared in Example and Comparative Examples 4-6 is shown. DETAILED DESCRIPTION

[0071] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0072] Example 1: Preparation of two-dimensional biocatalyst FeO-MoS2

[0073] Taking the preparation of Fe single-atom two-dimensional biocatalyst FeO-MoS2 as an example, the method includes (its synthesis schematic diagram is shown in Figure 1 shown):

[0074] S1.FeMo6O 24 Preparation of precursor: FeMo6O 24 The synthesis method is: (NH4)6Mo7O 24 ·4H2O (abbreviated as Mo7, 5.19 g, 4.2 mmol) was dissolved in water (80 mL) and heated to 100°C. Fe(NO3)3·9H2O (1.41 g, 3.5 mmol) was dissolved in water (20 mL) and then slowly added to the Mo7 solution under stirring. The pH of the mixed solution was maintained between 2.5 and 3, and the mixture was kept heated and stirred for 2 h to produce a dark brown solution. The crude product was separated by filtration, recrystallized twice in hot water (80°C), and finally dried at room temperature to obtain a light yellow FeMo6O 24 .

[0075] S2. Preparation of two-dimensional biocatalyst FeO-MoS2: 50 mg of FeMo6O 24 Dissolve 80 mg of thioacetamide (TAA) in 5 mL of deionized water and quickly add the thioacetamide solution to the FeMo6O 24 The solution was stirred at room temperature for 15 min. The mixed solution was then transferred to a 100 mL Teflon-lined autoclave, and the autoclave was reacted at 180 ° C for 24 h. After cooling to room temperature, the obtained black precipitate was washed three times with water and ethanol, and then vacuum dried at 60 ° C to obtain FeO-MoS2.

[0076] Comparative Example 1: Preparation of Fe / MoS2

[0077] Fe / MoS2 was prepared by the method described in S2 of Example 1, except that 50 mg of FeMo6O 24 Replaced with 17 mg of Fe(NO3)3·9H2O and 50 mg of Mo7.

[0078] Comparative Example 2: Preparation of MoS2

[0079] MoS2 was prepared by the method described in S2 of Example 1, except that 50 mg of FeMo6O 24 Replaced with 50 mg of Mo7.

[0080] Comparative Example 3:

[0081] FeO-MoS2 was prepared by the method described in Example 1, the only difference being that the thioacetamide in S2 was replaced by thiourea.

[0082] Comparative Examples 4-6:

[0083] XO-MoS2 is prepared by the method described in Example 1, the only difference being that the iron salt (i.e., Fe(NO3)3·9H2O) in S1 is replaced by the corresponding Mn salt, Cu salt or Co salt, thereby preparing MnO-MoS2, CuO-MoS2 or CoO-MoS2.

[0084] Experimental Example 1: Structural Characterization of FeO-MoS2

[0085] Taking the Fe single-atom two-dimensional biocatalyst FeO-MoS2 as an example, the microstructure of the material was first characterized by electron microscopy. Figure 2 The SEM images in the figure show that the synthesized materials all have a flat sheet structure. We further analyzed the spherical aberration electron microscope image of FeO-MoS2 and the element distribution map (EDX) at the atomic scale, such as Figure 3 As shown. The image shows that FeO-MoS2 has obvious layer wrinkles, indicating that the synthesized FeO-MoS2 is an ultra-thin two-dimensional sheet morphology, showing a relatively obvious crystal structure. At the scale of 3nm, it can be observed that Fe, Mo, and S are evenly distributed, proving the successful synthesis of FeO-MoS2. In addition, it is worth noting that we also found the characteristic image of the O element, which shows that the FeMo6O 24 The FeO-MoS2 obtained by sulfidation of the molecules retains a certain amount of O atoms.

[0086] HAADF-STEM imaging analysis was performed at the atomic scale. Figure 4 The atomic arrangement of FeO-MoS2 can be clearly observed, showing hexagonal intensity variations, which is consistent with the reported STEM images of monolayer 1T-MoS2. In addition, intensity variations in Fe and Mo can be observed in various regions of the sample. 24 The hexagonal unit of the precursor ( Figure 4The red dashed hexagons in a) are well preserved in the FeO-MoS2 nanosheets. In addition, we cut samples of random areas for analysis and built a 3D model to analyze the positions of Fe atoms, such as Figure 4 As shown in bc, due to the lower atomic number of Fe relative to Mo, the atomic intensity contour diagram shows the distribution of isolated low-intensity Fe atoms between high-intensity Mo atoms in the lattice, proving that the Fe atoms remain in the state of the precursor. After sulfidation, Fe is successfully incorporated into the MoS2 lattice.

[0087] We analyzed the phase state of the synthesized samples by Raman spectroscopy. Figure 5 As shown in Figure 2, FeO-MoS2 showed the 1T phase-related 148, 194, 236, 283, and 336 cm -1 The characteristic Raman peaks of 1T-MoS2 nanosheets were confirmed. In addition to the characteristic peaks of 1T phase, Fe / MoS2 and MoS2 also showed 380 and 405 cm -1 The characteristic Raman peak corresponds to E 1 2g A 1 g This proves that Fe / MoS2 and MoS2 are a mixed structure of 1T and 2H phases.

[0088] We used X-ray fluorescence spectroscopy (XPS) to analyze the bonding of the Fe site. Figure 6 As shown in a, the XPS fitting curve of Fe 2p of FeO-MoS2 can be divided into three main peaks, located at 707.58eV, 708.47eV and 709.70eV, belonging to Fe-S, Fe(II) and Fe(III) respectively. These characteristic peaks indicate the presence of Fe-S and Fe-O. According to the analysis of Fe-S and Fe-O ( Figure 6 b), for the Fe-S content, the content of FeO-MoS2 (60%) is less than that of Fe / MoS2 (67%), and for the Fe-O content, the content of FeO-MoS2 (40%) is more than that of Fe / MoS2 (33%), which further illustrates that there may be more O and Fe connected in FeO-MoS2, which may change the coordination environment of Fe atoms and further affect the catalytic performance of the material.

[0089] We used X-ray synchrotron radiation (XAS) to further explore the local coordination environment around Fe atoms. Figure 7 As shown in a, the normalized X-ray absorption near-edge structure (XANES) spectrum of the Fe K edge shows that the absorption edge of FeO-MoS2 is located between the absorption edge of the Fe standard sample and the absorption edge of Fe2O3, confirming that the valence state of Fe in it is between Fe 0and Fe 3+ We also quantitatively fit the Fourier transform X-ray absorption fine structure spectrum (EXAFS) of Fe, as shown in Figure 7 As shown in b, the results show that there are three coordination structures in FeO-MoS2: Fe-O, Fe-S and Fe-Mo. It is worth noting that the EXAFS fitting results of Fe / MoS2 ( Figure 7 c) shows that it has only two coordination structures: Fe-S and Fe-Mo. 24 The FeO-MoS2 synthesized in the framework structure will introduce O atoms to coordinate with Fe to form a Fe-S(O)-Mo coordination structure. The O / S regulation effect shortens the distance between Fe atoms and Mo atoms, which may cause changes in the energy band structure of Fe and further affect its catalytic performance.

[0090] These results indicate that a series of two-dimensional biocatalysts with atomically dispersed active sites were prepared through the strategy of polyoxometalate template method.

[0091] Experimental Example 2: Enzyme-like activity of FeO-MoS2

[0092] Peroxidase-like (POD) activity:

[0093] We measured the POD-like catalytic activity of the material by TMB method. Figure 8 As shown in the figure, after 10 min of reaction, the absorbance of pure MoS2 nanosheets at 652 nm is negligible, but after the addition of Fe element (Fe / MoS2), the catalytic system has an absorption peak of a certain intensity at 652 nm (I 625 nm =0.5), indicating that the Fe site is the catalytic active site. The FeO-MoS2 catalytic system with Fe-S(O)-Mo sites has the highest intensity absorption peak at 652nm (I 625 nm =1.1), demonstrating its efficient POD-like catalytic performance. Based on the Michaelis-Menten curve and the linear double reciprocal plot, we calculated the Michaelis-Menten constants (K m ) Maximum reaction rate (V max ), active center turnover number (TON), such as Fig. 9 Compared with the comparative sample Fe / MoS2(V max =1.01×10 -7 M.s -1 ; K m=1.40mM), FeO-MoS2 not only has a larger reaction rate (V max =1.57×10 -7 M.s -1 ), showing efficient catalytic kinetic characteristics and a small Michaelis-Menten constant (K m =1.33mM), showing a strong affinity for H2O2. In addition, we also calculated the TON values ​​of the two materials containing Fe sites. The results showed that FeO-MoS2 has a higher TON value (4.03s -1 ), indicating that the Fe active sites have higher reactivity after O / S regulation.

[0094] EPR spectroscopy and fluorescence probe methods can detect the types of ROS produced by materials. Fig.10 As shown in the figure, DMPO was used as a free radical scavenger for EPR experiments, and two split peaks were detected in the EPR spectrum of the FeO-MoS2 catalytic system, which were consistent with DMPO / ·OH and DMPO / ·O2 - The characteristic peaks of FeO-MoS2 catalytic system prove that the ROS produced are mainly ·OH and ·O2 - In addition, we used fluorescent probes to quantitatively test the generation of free radicals, such as Fig.10 As shown, O2 is detected by HE - We found that after excitation with 470nm light, the fluorescence intensity peaked at 610nm, and the peak of the FeO-MoS2 catalytic system was the strongest, indicating that the generated ·O2 - In addition, we also measured the production of ·OH by the TA method. By fluorescence spectroscopy, we confirmed that the FeO-MoS2 catalytic system can produce ·OH, and compared with the control sample, it produces the most ·OH. Therefore, we conclude that compared with Fe / MoS2 and MoS2, the FeO-MoS2 catalytic system has the best POD-like activity and can produce more ·OH and ·O2 - .

[0095] HPO-like activity:

[0096] HPO, or haloperoxidase, is also known as myeloperoxidase in the human body. It can catalyze the oxidation of halogen ions to generate highly oxidizing hypohalous acid, which plays a key role in the anti-biological pollution of marine algae and human immunity. It has excellent antibacterial, anti-biological pollution and anti-tumor application prospects. We use lapis lazuli blue to detect the production of hypochlorous acid. This method is based on measuring the oxidation of lapis lazuli blue (CB) by hypochlorous acid. After adding hypohalous acid, the absorbance of its solution system at 650nm decreases, and the weaker absorption peak at 520nm increases. CB method spectrum results ( Fig.12 ) shows that the absorbance of FeO-MoS2 at 520nm increases the most, and the absorbance at 650nm decreases the most, and the ratio of the absorbance at these two positions (I 520 nm / I 650 nm ), the relative HPO activity of the material can be further obtained. Statistics show that FeO-MoS2 has the highest HPO activity, indicating that it produces the most hypochlorous acid, which will also enhance the antibacterial properties of the material.

[0097] Experimental Example 3: Near-infrared photothermal conversion capability of FeO-MoS2

[0098] After discovering that the FeO-MoS2 catalytic system with O / S-tuned Fe-S(O)-Mo sites exhibits excellent POD-like and HPO-like catalytic activities, we also verified the near-infrared photothermal conversion capability of FeO-MoS2.

[0099] Near infrared thermal performance test:

[0100] In order to study the near-infrared photothermal conversion ability of FeO-MoS2, a near-infrared laser at 808 nm was used to irradiate the FeO-MoS2 suspension, and an infrared camera was used to record the heating process of the material. Specifically, the material was dispersed in 1 mL of deionized water, and then a near-infrared laser (PSU-III-LRD, 808 nm) was used to irradiate the material suspension (power density was 2.5 W cm -2 , irradiation distance of 5 cm, irradiation time of 10 min). At the same time, the temperature change of the suspension was tracked and recorded every two minutes using an infrared camera TH9100. The temperature measurement was repeated at least 3 times to take the average value to reduce the experimental error.

[0101] like Fig.13As shown in ab. In a 1mL material suspension system, the temperature of Fe / MoS2, MoS2 and FeO-MoS2 under near-infrared (NIR) irradiation was detected as a function of irradiation time. After 10 minutes of NIR irradiation, the temperature of FeO-MoS2 and its comparison sample can reach 55°C, proving that the material has near-infrared photothermal conversion performance, which provides the possibility for its photothermal delivery of ROS. In addition, in order to further eliminate the influence of NIR light on ROS production performance, we also used the TMB method to test the POD-like activity of the material under near-infrared light. As shown Fig.12 As shown in (c), after NIR irradiation, FeO-MoS2 has similar POD-like activity to the Control group without NIR irradiation, indicating that NIR irradiation does not cause an increase in the POD-like activity of the material.

[0102] Experimental Example 4: Antibacterial activity of FeO-MoS2

[0103] After verifying that the material has near-infrared photothermal conversion capabilities, we selected methicillin-resistant Staphylococcus aureus (MRSA) as a model bacterium, induced it to form a biofilm, and studied the photothermal mass delivery effect of the two-dimensional sheet material FeO-MoS2 on the biofilm.

[0104] Photothermal-induced reactive oxygen species delivery and anti-biofilm testing:

[0105] The anti-biofilm ability of FeO-MoS2 catalytic system was studied using methicillin-resistant Staphylococcus aureus (MRSA, ATCC 43300, Gram-positive) as a model bacterium. First, biofilm culture was performed. 195 μL of liquid culture medium and 5 μL of MRSA bacterial solution (10 8 CFU·mL -1 ) was added to a 96-well plate and incubated at 37°C for 24 h to form a biofilm. For the crystal violet experiment, the material suspension was added to a 96-well plate containing a biofilm to form a certain concentration gradient (40, 80, 120, 160, 200, 240, 280 and 320 μg mL -1 ), and H2O2 solution was added at the same time, so that 200 μL of the system contained 0.4 mM H2O2, and then the above 200 μL biofilm / material system was irradiated with a near-infrared laser (PSU-III-LRD, 808 nm) (power density was 2.5 W·cm -2, irradiation distance was 5 cm, irradiation time was 10 min), after irradiation, culture was continued for 2 h, then the liquid in the well plate was aspirated, washed twice with saline, stained with 0.1% crystal violet for 10 min, then washed once with saline, 100% ethanol was added to dissolve the crystal violet, and the absorbance value at 570 nm was measured using an enzyme reader to determine the biomass.

[0106] After biofilm formation, FeO-MoS2 and red fluorescent (rhodamine B-isothiocyanate) labeled 10 kDa dextran (RD10) were added to the confocal wells containing MRSA biofilms and the cells were illuminated with 2.5 W cm -2 After 10 min of NIR irradiation, DAPI stain was added. Confocal images and red fluorescence intensity statistics are shown in Figure 2. Fig.14 and 15 As shown, there is almost no RD10 red fluorescence in the H2O2 group, indicating that the ROS-producing activity of the material alone can hardly change the permeability of the biofilm and bacterial membrane structure, and it is difficult for substances to enter the bacteria. After the introduction of NIR irradiation, the red fluorescence intensity increased significantly, and the blue fluorescence used to mark bacteria and the delivered red fluorescence can be co-localized, which shows that RD10 can enter the bacteria. For the H2O2+NIR group, the red fluorescence was further enhanced, which shows that the temperature change and ROS production caused by near-infrared light can greatly change the permeability of the biofilm and bacterial membrane structure, further enhancing the substance delivery process. In summary, the photothermal effect of the sheet material FeO-MoS2 has the potential for substance delivery, which provides great possibilities for subsequent ROS delivery.

[0107] In addition, we also used the fluorescent probe C11-BODIPY of LPO 581 / 591 The oxidation state of the bacterial membrane structure in the biofilm was studied (red fluorescence marked normal membrane structure (LM), green fluorescence marked peroxidized lipid molecules (LPO)), to prove that ROS can be delivered to the bacterial membrane structure and can cause peroxidation of the membrane structure. Specifically, the biofilm was cultured on a 24-well confocal plate using the above method. After the biofilm was formed, a certain amount of material solution and hydrogen peroxide solution were added, and then a near-infrared laser (PSU-III-LRD, 808nm) was used to irradiate the above biofilm / material system (power density was 2.5W·cm -2 After irradiation, the samples were washed with saline, stained with DAPI, and stained with C11-BODIPY at a concentration of 5 mM. 581 / 591The dye working solution was used for staining for 20 min, and images were obtained using CLSM (St5, Leica). Rhodamine B isothiocyanate–Dextran was used to study photothermal-induced material delivery. Specifically, the biofilm was cultured on a 24-well confocal plate using the above method. After the biofilm was formed, a certain amount of material solution and hydrogen peroxide solution were added, and Rhodamine B isothiocyanate–Dextran was added to make its concentration in the biofilm / material system 2 mg·mL -1 Then, a near-infrared laser (PSU-III-LRD, 808 nm) was used to irradiate the biofilm / material system (power density was 2.5 W·cm -2 , irradiation distance was 5 cm, irradiation time was 10 min). After irradiation, the MRSA biofilm was washed once, stained with DAPI, and images were obtained using CLSM (St5, Leica).

[0108] like Fig.16 and 17 As shown in the figure, confocal fluorescence images and green fluorescence statistics show the LPO levels of bacteria in each group of biofilms. After adding H2O2, there was basically no peroxidation in the membrane structure of the bacteria, but when FeO-MoS2 and H2O2 were added, the LPO level increased slightly, which shows that the protective effect of EPS of the biofilm on the bacteria inside prevented ROS from directly acting on the bacterial membrane structure, so the LPO level was low. After the introduction of FeO-MoS2 and NIR, the LPO level was slightly higher than that of the FeO-MoS2+H2O2 group, indicating that heat can also cause certain oxidative stress, thereby slightly increasing the LPO level, but no ROS is produced, which limits the increase in the LPO level. The LPO level of the FeO-MoS2+H2O2+NIR group increased significantly, significantly higher than that of the other groups. This is because the sheet material can generate heat under NIR irradiation, and can convert H2O2 into ROS, which significantly enhances the permeability of the biofilm. ROS can be directly delivered to the surface of bacteria, thereby attacking the cell membrane lipids and causing them to peroxidize.

[0109] After studying the efficient ROS delivery of the material, we further analyzed the photothermal anti-biofilm effect of the material. We used the classic crystal violet method to study the anti-biofilm effect of the FeO-MoS2 material, such as Fig.18We used different concentrations of materials to treat the biofilm, and then stained it with crystal violet. The absorbance can reflect the anti-biofilm performance of the material. The results show that with the increase of material concentration, the anti-biofilm effect of FeO-MoS2 is more significant. When H2O2 (+H) and NIR (+N) are introduced at the same time, the anti-biofilm effect of FeO-MoS2 is at a material concentration of 40μg·mL -1 After that, the absorbance remained basically unchanged, and this absorbance was considered to be a sign that the biofilm was basically eliminated. -1 is the lowest concentration of FeO-MoS2+H2O2+NIR against biofilm. Therefore, the lowest concentration of FeO-MoS2+H2O2 against biofilm is 240 μg mL -1 The lowest concentration of FeO-MoS2+NIR against biofilm is 200 μg·mL -1 This further illustrates that, under the condition of only H2O2 or NIR, although the material can achieve the effect of removing biofilm, it requires extremely high material concentration, which may cause serious cytotoxicity or metabolic problems. However, when NIR and ROS are introduced at the same time, its efficient ROS production and delivery enable the material to achieve the effect of removing biofilm at a lower concentration (40 μg mL -1 ) can achieve better anti-biofilm effect, greatly avoiding the problem of excessive material consumption.

[0110] Therefore, we selected 40 μg mL -1 The subsequent anti-biofilm experiment was carried out with the material concentration of , and the near-infrared photothermal effect at this material concentration was first determined, such as Fig.19 As shown. A near-infrared camera was used to record the temperature change of the liquid in the 96-well plate. After 10 minutes of NIR irradiation, the liquid temperature of the system can reach about 45°C. At this temperature, the heat generated by the material locally in the biofilm will directly act on the biofilm, causing the EPS to loosen and the biofilm permeability to increase, thereby achieving the effect of ROS delivery.

[0111] To further investigate the anti-biofilm mechanism of materials under different treatment conditions, we used the microscopic spatial distribution and structure of biofilm components to conduct anti-biofilm tests by using a multi-labeling method with bacteria-specific fluorescent probes. Specifically, EPS, live bacteria, and dead bacteria of biofilms were labeled using EPS probes (Dextran Alexa Fluor 647), SYTO-9, and PI, respectively. After different treatments, CLSM was used for observation, e.g. Fig. 20As shown. The image shows that the biofilm of the Control group has a strong green fluorescence, indicating that the bacteria under the protection of EPS are live bacteria, and its EPS (blue) is clustered and distributed between the bacteria, indicating that the biofilm is relatively complete, forming a cohesive and densely arranged microbial structure. After only the introduction of H2O2, the FeO-MoS2+H2O2 group maintained a green fluorescence intensity similar to that of the Control group, and the blue fluorescence intensity was weakened, indicating that the EPS level was reduced. ROS can degrade part of the EPS, but due to the tight structure of EPS, ROS cannot be effectively delivered to the bacterial surface, resulting in a large number of bacteria. After only the introduction of NIR irradiation, the number of green and red fluorescent-labeled bacteria in the FeO-MoS2+NIR group decreased, and the blue fluorescence intensity was weakened, indicating that the EPS level decreased significantly, which shows that NIR can make the EPS structure loose and the bacteria fall off, which is consistent with the crystal violet staining results, but due to the lack of ROS delivery, its bactericidal effect is not very obvious, and there are still some live bacteria. In sharp contrast to the other two, most of the bacteria in FeO-MoS2+H2O2+NIR are dead and arranged more sparsely, with only a small amount of EPS distribution detected, which further illustrates the anti-biofilm mechanism of the material, that is, NIR irradiation can loosen the EPS of the biofilm, and then the highly toxic ROS produced by the catalysis of the material can be directly delivered to the bacterial surface, directly interacting with the bacteria to achieve the antibacterial purpose.

[0112] Experimental Example 5: Evaluation of cell compatibility and toxicity of FeO-MoS2

[0113] Cytocompatibility evaluation:

[0114] We selected human umbilical vein endothelial cells (HUVECs) as a model to verify the cell compatibility of the material. Fig.21 As shown, we first incubated the cells with MoS2, Fe / MoS2 and FeO-MoS2 in the presence of H2O2 for different time periods. The material concentrations were those of the anti-biofilm experiment. Then, the cell survival was determined by live / dead fluorescence staining experiments. For the pure HUVECs group and the MoS2+H2O2, Fe / MoS2+H2O2, and FeO-MoS2+H2O2 groups, we can notice that although there are some dead cells, most of the cells are alive, and after long-term culture, the cells will continue to proliferate, which indicates that the material has limited toxicity to cells and will not affect cell activity for a long time.

[0115] We also studied the cytotoxicity of the synthesized 2D sheets under NIR irradiation. Fig. 22After NIR irradiation, there were cell deaths in the MoS2+H2O2, Fe / MoS2+H2O2 and FeO-MoS2+H2O2 groups, indicating that the temperature increase caused by NIR irradiation did have certain cytotoxicity, but the cells did not die completely. After 48 hours of culture, the number of HUVECs gradually recovered, indicating that the long-term effect of near-infrared irradiation on living cells was limited.

[0116] Experimental Example 6: Anti-infection study of FeO-MoS2 in rabbits

[0117] Study on the anti-infection of FeO-MoS2 nanosheets in rabbits:

[0118] We further verified the feasibility of FeO-MoS2 as a treatment for MRSA biofilm infection in vivo through wound disinfection experiments. We first cut a 1 cm diameter skin from the experimental rabbit epidermis and introduced MRSA (100 μL, concentration: 1×10 8 CFU·mL -1 ) infected wounds, and to evaluate the in vivo anti-biofilm effect of FeO-MoS2+H2O2+NIR, H2O2, FeO-MoS2+H2O2, and FeO-MoS2+NIR were used as control groups. In addition, we also tested the effect of vancomycin as a typical clinical antibiotic against MRSA.

[0119] We used cameras to record the entire process of wound healing, such as Fig.23 As shown, after 1 day of MRSA infection, abscesses formed in the wound, indicating MRSA colonization and biofilm formation. On the second day, different treatments were applied and a thermal imaging camera was used to monitor the NIR-induced temperature rise of FeO-MoS2, as shown in Figure 2. Fig.24 As shown. Due to the strong photothermal conversion ability of FeO-MoS2, after 2 minutes of irradiation (2.5W·cm -2), the temperature rose rapidly to 55°C. During this process, the material can exert excellent catalytic properties and photothermal effects without causing skin burns. The temperature change detected in the Control group was very limited, and only reached 42°C after 2 minutes of NIR irradiation. At this temperature, the bacteria can still maintain a certain activity. The wounds treated with saline, H2O2, FeO-MoS2+H2O2 and FeO-MoS2+NIR remained swollen until the 4th day, and the degree of closure was very limited. In contrast, the abscess disappeared and the wound area was significantly reduced in the wounds treated with vancomycin or FeO-MoS2+H2O2+NIR. It is worth noting that on the 12th day, the wounds in the vancomycin and FeO-MoS2+H2O2+NIR treatment groups had fully recovered. The closure speed of the saline, H2O2, FeO-MoS2+H2O2 and FeO-MoS2+NIR treatment groups was much slower, especially the large wounds in the saline and H2O2 treatment groups exposed different degrees of swollen epidermis, indicating that there was still severe inflammatory response in the wounds of the experimental rabbits.

[0120] In addition, after treatment, we also collected bacteria from the wound surface and used agar plate counts to detect the growth of bacteria in the wound ( Fig.25 ). There were almost no bacterial colonies in the wounds treated with vancomycin or FeO-MoS2+H2O2+NIR, indicating that the FeO-MoS2 biocatalyst can achieve efficient bactericidal activity comparable to the effect of antibiotics after H2O2+NIR treatment. In contrast, there were still a large number of live bacteria in the Control group, H2O2 group, FeO-MoS2+H2O2 group, and FeO-MoS2+NIR group, indicating that its wound disinfection ability was limited. The above results show that our material can achieve efficient catalytic bactericidal ability comparable to antibiotics, which is beneficial to reduce the bacterial load at the wound and promote rapid wound healing.

[0121] On the 12th day, we extracted peripheral blood from the experimental rabbits for analysis, focusing on indicators related to bacterial infection, namely white blood cell (WBC) and neutrophil (NEU) counts, such as Fig.26As shown in the figure, the counts of the Control group and the H2O2 group showed that there were still a large number of WBC and NEU in the blood of the experimental rabbits, proving that the wound was still an inflammatory environment of bacterial infection. The WBC and NEU counts of the FeO-MoS2+H2O2 group were reduced, lower than those of the Control group and the H2O2 group, indicating that the inflammatory environment was alleviated, but still relatively serious. The WBC and NEU counts of the FeO-MoS2+H2O2+NIR and vancomycin groups were significantly lower than those of the other groups. These results show that FeO-MoS2+H2O2+NIR can effectively remove MRSA from the wound surface of rabbits, promote wound healing, and reduce obvious inflammatory reactions.

[0122] In addition, to understand the wound recovery status, we performed pathological analysis on wound tissue sections by hematoxylin-eosin (H&E) staining. Fig. 27 As shown in a, the Control group and the H2O2 group showed large-area neutrophil infiltration (indicated by the blue arrow) and necrotic cells (indicated by the black arrow), which indicated that the inflammatory response of the MRSA-infected wound had not recovered. At the same time, the texture of the interstitial collagen fibrils was disordered, showing the characteristics of severe wound infection. The FeO-MoS2+H2O2 and FeO-MoS2+NIR groups also showed neutrophil infiltration and disordered texture of collagen fibrils, indicating that the simple production of ROS and heat could not completely kill bacteria, and there was still a bacterial load in the wound, which slowed down the speed and quality of wound healing. After treatment with FeO-MoS2+H2O2+NIR, the typical inflammatory area disappeared, and a large number of dermal fibroblasts (indicated by the green arrow) appeared. The regular arrangement of collagen fibrils verified the rapid and effective wound disinfection ability of FeO-MoS2+H2O2+NIR, which can make the wound heal quickly. More importantly, the wounds treated with FeO-MoS2+H2O2+NIR had similar pathological features to those treated with vancomycin and were similar to normal tissues, so we can conclude that the FeO-MoS2+H2O2+NIR system has certain application prospects in antibiotic-free treatment.

[0123] In addition, we performed Masson's trichrome staining to investigate collagen recovery during wound healing. Fig. 27 (b) and 28(a), the FeO-MoS2+H2O2+NIR group showed extensive and well-organized collagen deposition, with the highest collagen volume fraction (68.14%), which was similar to that of the vancomycin group (71.87%), much higher than that of the Control group (26.96%) and the H2O2 group (29.86%), and also better than the FeO-MoS2+H2O2 group (40.07%) and the FeO-MoS2+NIR group (42.02%).

[0124] The wound healing process is usually accompanied by the regeneration of new blood vessels. The more regenerated blood vessels, the better the blood transport to the wound and the better the wound recovery. With the help of CD31 immunohistochemical staining and DAPI and CD31 immunofluorescence staining, we can observe the formation of new blood vessels during wound repair, such as Fig. 27 (c, d). We achieved this through fluorescent staining of CD31. There were very few CD31-positive cells in the Control group and the H2O2 group, and the CD31 expression rates were (14.29%) and (15.66%), respectively. The FeO-MoS2+H2O2 group and the FeO-MoS2+NIR group had increased CD31-positive cells, while the FeO-MoS2+H2O2+NIR group and the vancomycin group showed further increased CD31 expression, which were 66.67% and 70.95%, respectively, showing the best wound healing effect. In addition, we used CLSM imaging and CD31 immunofluorescence staining to achieve 3D reconstruction of the new blood vessels. The reconstruction showed that the FeO-MoS2+H2O2+NIR group (80.79 vessels·mm -2 ) and vancomycin group (82.14 vessels·mm -2 ) had the largest number of new capillaries, indicating better wound healing. These data suggest that the FeO-MoS2+H2O2+NIR system can effectively remove bacteria from wound sites in vivo and promote angiogenesis, thereby achieving better wound repair ability.

[0125] In addition, to further verify the biocompatibility of the material, we also performed H&E staining on the main organs (heart, liver, spleen, lung, and kidney) of the experimental rabbits treated with FeO-MoS2+H2O2+NIR ( Fig.29 ), no obvious damage or abnormalities were found in these tissue sections, indicating that the FeO-MoS2+H2O2+NIR treatment method is biosafe.

[0126] Experimental Example 7:

[0127] The material of Comparative Example 3 using thiourea was characterized by electron microscopy. The results are as follows: Fig.30 As shown, we can see the nanoflower structure synthesized using thiourea, which shows that thioacetamide is the key to synthesizing sheet materials. If thiourea is used, products with other morphologies will be obtained.

[0128] As described in Experimental Example 2, the POD-like catalytic activities of the materials prepared in Example 2 and Comparative Examples 4-6 were compared by TMB method. Fig.31 As shown, it can be seen that only FeO-MoS2 has good POD-like catalytic performance, while the performance of the other XO-MoS2 is poor.

[0129] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A two-dimensional antibacterial biocatalyst with photothermal conversion capability, characterized in that: The two-dimensional antibacterial biocatalyst is a 2D MoS2 nanosheet doped with Fe single atoms and introduced with O atoms to coordinate with Fe.

2. The two-dimensional antibacterial biocatalyst with photothermal conversion capability according to claim 1, characterized in that: The 2D MoS2 nanosheets doped with Fe single atoms and introduced with O atoms to coordinate with Fe have a 1T phase structure and contain Fe-O, Fe-S and Fe-Mo coordination structures.

3. The two-dimensional antibacterial biocatalyst with photothermal conversion capability according to claim 1 or 2, characterized in that: The two-dimensional antibacterial biocatalyst is prepared as follows: (1)FeMo6O 24 Preparation of precursor: (NH4)6Mo7O 24 4H2O reacts with Fe salt in water under heating and pH 2.5-3 to obtain FeMo6O 24 Precursor; (2) Preparation of two-dimensional antibacterial biocatalyst FeO-MoS2: FeMo6O 24 The precursor reacts with thioacetamide in water under heating conditions to obtain a two-dimensional antibacterial biocatalyst FeO-MoS2.

4. The two-dimensional antibacterial biocatalyst with photothermal conversion capability according to claim 3, characterized in that: The Fe salt in step (1) includes Fe(NO3)3·9H2O; Further, the reaction in step (1) is carried out at 80-100°C; Furthermore, step (1) further comprises collecting the crude product by filtration after the reaction is completed, recrystallizing it in hot water, and then drying it; Furthermore, the reaction in step (2) is carried out at 160-200°C.

5. Use of the two-dimensional antibacterial biocatalyst with photothermal conversion capability according to any one of claims 1 to 4 in the preparation of an enzyme-mimicking preparation, characterized in that: The enzyme-mimicking preparation is a peroxidase-mimicking preparation and / or a haloperoxidase-mimicking preparation.

6. Use of the two-dimensional antibacterial biocatalyst with photothermal conversion capability as claimed in any one of claims 1 to 4 in the preparation of an antibacterial system.

7. The use according to claim 6, characterized in that: The antimicrobial system also includes H2O2.

8. The use according to claim 6, characterized in that: The antibacterial system also includes a near infrared light system.

9. The use according to claim 6, characterized in that: The antibacterial system also includes H2O2 and near-infrared light irradiation system.

10. An antimicrobial system, characterized in that: The antibacterial system comprises a two-dimensional antibacterial biocatalyst having photothermal conversion capability as described in any one of claims 1 to 4; Preferably, the antimicrobial system further comprises H2O2; Preferably, the antibacterial system further comprises a near-infrared illumination system; Preferably, the antibacterial system also includes H2O2 and near-infrared light system; Preferably, the antimicrobial system is an antimicrobial system against biofilm.